The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32710/tekstilvekonfeksiyon.621184
|View full text |Cite
|
Sign up to set email alerts
|

An Image Processing Research Consistent With Standard Photographs to Determine Pilling Grade of Woven Fabrics

Abstract: In this study, MATLAB 2018a software was used to evaluate pilling grade of woven fabrics objectively. Experimental works were carried out on the EMPA W3 standard photographs and accordingly two woven fabrics. Equations were built based on the measurements of pill characteristics and textural parameters of these photographs with the help of curve fitting method after image processing steps. Intervals were generated for each fabric by using slope of these equations and quantitative parameters obtained from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Mean of matrix elements, standard deviation of matrix elements and entropy of grayscale imagesfrom textural parameters were used in a limited number of previous studies. Telli (2019) and Telli (2020) indicated that success has been achieved by using means of matrix elements in their developed method to determine the pilling grade of fabrics [27][28]. In this study, these three textural parameters showed strong correlation over 0.75 with all Zweigle indices in the Sobel and Prewitt methods.…”
Section: Figure 2images After Edge Detection Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…Mean of matrix elements, standard deviation of matrix elements and entropy of grayscale imagesfrom textural parameters were used in a limited number of previous studies. Telli (2019) and Telli (2020) indicated that success has been achieved by using means of matrix elements in their developed method to determine the pilling grade of fabrics [27][28]. In this study, these three textural parameters showed strong correlation over 0.75 with all Zweigle indices in the Sobel and Prewitt methods.…”
Section: Figure 2images After Edge Detection Methodsmentioning
confidence: 58%
“…After, these matrices in "1000x2500 uint8" format were transformed to double (1000x2500 double) format. A median filter was implemented on matrices in this format and image intensity values were adjusted for edge detection by using histogram-fitting [27,28]. Then, edge detection was applied in seven different methods.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of parameters influence pilling in knitted and woven fabrics, like type of fibres, shape of fibres, fibre staple length, spinning technology used to produce the yarn, fabric construction, finishing technology, etc. All these parameters influence the pilling tendency of a garment [4]. Knitted fabrics tend to pill more readily than woven fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase use of synthetic fibers and their blends in recent decades, the importance of pilling has increased even more [4]. In example polyester fabrics have excellent properties such as high strength, attractive hand, dimensional stability and easy-care properties.…”
Section: Introductionmentioning
confidence: 99%